A new MAPT deletion in a case of speech apraxia leading to corticobasal syndrome. Issue 3 (4th May 2018) - Mazzon, Giulia; Menichelli, Alina; Fabretto, Antonella; Cattaruzza, Tatiana; Manganotti, Paolo
ABSTRACT: Speech apraxia is a disorder of speech motor planning/programming leading to slow rate, articulatory distortion, and distorted sound substitutions. We describe the clinical profile evolution of a patient presenting with slowly progressive isolated speech apraxia that eventually led to the diagnosis of corticobasal syndrome (CBS), supporting the evidence that this rare speech disorder can be the first presentation of CBS. Moreover, we found a novel variant in MAPT gene, which is hypothesized to be disease-causing mutation. These results underscore the importance of genetic analysis – particularly in selected atypical cases – for in vivo understanding of possible pathophysiological disease process.